Guías de atención médica para dejar de fumar. Una propuesta para Latinoamérica Proposal of Latin-American guidelines for smoking cessation - Raúl H Sansores; Oliver Pérez-Bautista; Alejandra Ramírez-Venegas (Instituto Nacional de Salud Pública, 2010)
Objetivo. Aunque la prevalencia del tabaquismo es diferente en cada país de América, los daños a la salud se presentan en la misma proporción. Por ello, es indispensable contar con guías de tratamiento que idealmente sean de utilidad para todos los países. Material y métodos. Para hacer recomendaciones puntuales de utilidad a la región se realizó una búsqueda en PubMed de los últimos cinco años, con los títulos "Smoking cessation guidelines" y "Smoking cessation treatment meta-analysis" para conocer el contenido de las diferentes guías y de los títulos "Nicotine replacement therapy", "Nicotine chewing gum", "Nicotine patches" "Nicotine inhaler", "Bupropion therapy", "Varenicline therapy" e "Individual and grupal behavioural counselling for smoking cessation" para determinar la eficacia de cada intervención. Resultados y conclusión. Nuestra recomendación basada en la disponibilidad de medicamentos y de recursos humanos es que el consejo médico y la terapia conductual grupal deben ser acciones primarias acompañadas, o no, de medicamentos de primera línea. Objective. Although prevalence of tobacco smoking is different in the Latin American regions, the consequences on health are similar. Material and Methods. Therefore, guidelines on treatment are needed and ideally speaking must be useful in the different countries. In order to make quick recommendations useful in the region we made a search in PubMed from the last 5 years with the titles "Smoking cessation guidelines" and "Smoking cessation treatment meta-analysis" to know the content of different guidelines and with the titles of "Nicotine replacement therapy", "Nicotine chewing gum", "Nicotine patches", "Nicotine inhaler", "Bupropion therapy", "Varenicline therapy" and "Individual and grupal behavioural counselling for smoking cessation" to determine the efficacy of each intervention. Results and conclusion. Our recommendation based on the availability of pharmacotherapy and human resources is that medical advice and behavioural grupal counseling must be primary interventions either adding, or not, first line drugs for smoking cessation